Applaying Transition Action Detail Strategy on Written Text of EFL Young Learners - Yeasy Agustina Sari; Suhono Suhono (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2017)
Mastering English, as foreign language need a lot of time since it is a continuing process. English foreign language of young learners, however, can’t be mastered by memorizing. The young learners should have strategy, which can be used as the direction of the classroom activites to help the students enhancing of language skill, specially in writting. There were the problem to be solved in this study, namely the students have difficult to construct the written text. The strategies which were used in the learning process were boring. Hence, the researcher tried to solve students’ difficulty in written text through Transition Action Detail Strategy. This study focused on two variables. The independent variable was Transition Action Detail Strategy, meanwhile dependent variable was written text. The researcher used true experimental design which consist of control group and experimental group. The subject of this research was students of young learner at the eight grade of English Course at Payakumbuh. The result revealed that Transition Action Detail Strategy was a good strategy that can influence the students’ narrative text. By using df.70, the writer not found it in the table. Because 70 was higher than 60 and smaller than 120. Then, the results from interpolation by using df.70, it could be known that the critical value of t-table for the 5% level was 1.990, the critical value of t-table for the 1% level was 2.638. From these all the data analysis, it can be seen that t-observed (4.763) was higher than t-table (5% =1.990, 1% = 2.638). The data confirm that t-observed is higher than t-table, therefore it can be inferred that Ha is accepted and Ho is rejected. It means that there is significant influence of applying Transition Action Detail Strategy on Wwritten Text of Young learners. Key words: Transition Action Detail Strategy, Young Learners, English Foreign Language, English Course.